ChemInform Abstract: Total Synthesis of (+)‐Asperolide C by Iridium‐Catalyzed Enantioselective Polyene Cyclization. Issue 16 (22nd April 2014) - Jeker, Oliver F.; Kravina, Alberto G.; Carreira, Erick M.
Abstract The first total synthesis of the target compound is described.